Layered Metal-Organic Frameworks Based on Octahedral Lanthanides and a Phosphonate Linker: Control of Crystal Size - Paz, Filipe A. Almeida
The hydrothermal reaction between lanthanide salts and residues of (benzene-1,3,5-triyltris(methylene))triphosphonic acid (H(6)bmt) promotes the formation of a new series of isotypical layered lanthanideorganic frameworks (LnOFs), [Ln(2)(H(3)bmt)(2)]center dot H2O [where Ln(3+) = Eu3+ (1), Gd3+ (2), Tb3+ (3), Dy3+ (4), Ho3+ (5), Er3+ (6), Tm3+ (7), and Yb3+ (8)]. The crystal structure was unveiled from powder X-ray diffraction data (both laboratory and synchrotron) in tandem with other characterization techniques (namely thermogravimetry, thermodiffractometry, vibrational spectroscopy, and elemental analysis). It is shown that the lanthanide contraction leads, on average, to a reduction of the average crystallite size, up to the nanometer scale in the case of compound 8. The unique structural features of the (2)(infinity)[Ln(2)(H(3)bmt)(2)] layers are discussed in detail, in particular, the six-coordination environment of the lanthanide cations and its topological relationship with the formation of the first 5,5L4 binodal network based on chelating phosphonate groups.